Controls on the dedolomitization of top of Villa Mónica Formation, Tandilia System - Ferreyra, Camila (2023)
Dedolomitization is the process of replacement of dolomite by calcite which mostly occurs under meteoric water influence. The shallow marine deposits of the Villa Mónica Formation (VMF) (~1150-720 Ma) constitute here is a good example of where to study this process. VMF is the older unit of the sedimentary basin infill in Tandilia System (Buenos Aires, Argentina), and it is formed by a lower section (22 m) mainly composed of quartz-arkosic sandstones, and an upper mainly dolomitic section (36-52 m) with thin interbedded green claystone levels and ending with red claystone and purple marl. The contact between the top of VMF and the base of the Colombo Formation is an erosive surface. Previous studies indicate that the VMF was affected by deep burial diagenesis followed by telogenesis. However, the expression of the weathering processes over the dolostones is poorly known. Thus, the proposal of this work is to recognize and characterize features related to weathering processes in the last meters of the upper section of the VMF.